Tokopedia and Komunikasi Berasa: The Case of ‘Filosofi Pete’ Campaign - Saroso, Dhea Andita Sari; Paramitha, Ni Ajeng Riandia; Putra, Denny Suwarso; Matahari, Frisky Freny; Fudholi, Ata; Senjatiana, Ferdy; Hadinugroho, Farid (Graduate School of Communication Universitas Bakrie, 2023)
Komunikasi Berasa (experientially-meaningful communication) is communication that synergizes messages and experiences with messages by creating a supportive atmosphere that creates deep meaning and impressions. This article analyzes Tokopedia's TVC advertising campaign version of